Assessing perspectives on the efficacy of digital tools in managing recreation parks in Tirana: A case study - Lile, Anduela; Kushta, Entela; Kacurri, Arben (Edelweiss Applied Science and Technology, 2025)
The research aims to investigate on the effects of introducing technological advances in the management of urban parks and other recreational spaces in the city. Local government parks and recreation management, an industry that has strived to focus on the benefits of outdoor activities and the simplicity of nature for decades is experiencing a paradigm shift because of technological innovation. This is affecting not only how local governments interact with and engage the public, but also the services offered by parks, recreation departments and other institutions. For the purpose of gathering community-specific information about the requirements and perspectives of recreation parks in the municipality of Tirana, a focus group was organized with recreation administrators, physical activity trainers, fitness specialists, entertainers, smart technology specialists, and representatives from the local leisure and recreation businesses. The qualitative data obtained from the focus group were grouped into patterns and themes, and were then examined using content analysis. Based on the findings, parks and recreation facilities can potentially improve facility adoption, profitability, and engagement with a range of generations even if only a few basic tech solutions are implemented. Local parks and recreation leaders may help engage the next generation of the community and highlight the value of park facilities in the community by getting visitors involved in activities that combine technology and outdoor exploration.